The effects of leadership behaviors on organization agility: a quantitative study of 126 U.S.-based business units - Gagel, Gretchen, author; Chermack, Thomas J., advisor; Korte, Russell, committee member; Gloeckner, Gene, committee member; Mumford, Troy, committee member (Colorado State University. Libraries, 2018)
Organizations face challenges related to swiftly and successfully adapting their products and services to meet the changing demands of the external environment to achieve long-term success. These challenges have prompted the study of organization agility, an organizational capability defined as the ability to swiftly and successfully change in order to achieve long-term financial success (Worley, Williams, & Lawler, 2014). Researchers have theorized that the behaviors and attributes of organization leaders impact organization agility (Worley et al., 2014; Holbeche, 2015). The purpose of this study was to conduct an inferential quantitative research study to determine if leadership behaviors predict organization agility. The research sample included 126 U.S.-based business units within 47 organizations with greater than 1,000 employees. Organization agility was measured using the Agility Survey (short-form) developed by Worley, Williams, and Lawler (2014) to generate a Total Agility Score. The leadership behaviors and attributes of the business unit leaders were measured using the Multifactor Leadership Questionnaire (MLQ-5X; Avolio & Bass, 2004). Confirmatory and exploratory factor analysis determined an alternative five-construct model of leadership behaviors and attributes for this data set. Simultaneous linear regression determined that the leadership behaviors found to predict higher levels of organization agility included (a) exploratory behaviors that support a culture of discovering new ways to solve problems and conduct business, (b) latitude behaviors that provide employees with a high degree of freedom and responsibility in achieving work results and resolving issues, (c) visionary behaviors that create a clear organization purpose and mission that define the "why" of the organization's existence, and (d) reflective behaviors that cause leaders to challenge their own assumptions and create mechanisms for the organization to do so as well. Simultaneous linear regression analysis also determined that leadership behaviors related to power and structure predict lower levels of organization agility. In addition to the original research question, results were reported comparing the Total Agility Score for organization groups divided by type of organization, size of organization, and year founded; and for business unit groups divided by business unit leader gender and size of business unit. Inspection of these results' means indicated that the Total Agility Score for for-profit organizations (M = 3.97) was significantly higher than the Total Agility Score for nonprofits/government agencies (M = 3.67), a difference of .30 on a 5-point Likert scale (p = .009) and with a larger than typical effect size (d = .77). Inspection of the results also indicated that the Total Agility Score for organizations with 1,000 to 6,000 employees (M = 3.99) was significantly higher than the Total Agility Score for organizations with greater than 6,000 employees (M = 3.83; p = .038) with an effect size between smaller than typical or medium (d = .37). This research study contributes to the body of knowledge of organization agility by informing scholars, practitioners, and organization leaders as to the leadership behaviors and attributes that predict both higher and lower levels of organization agility. Several additional research studies are suggested that would enhance knowledge related to the conceptual frameworks and theories of organization agility and leadership.
Keywords: change management; leadership; agility; organization agility; leader behaviors